Mismatch Brain Response to Speech Sound Changes in Rats - Ahmed, Mustak; Mällo, Tanel; Leppänen, Paavo H.; Hämäläinen, Jarmo; Äyräväinen, Laura; Ruusuvirta, Timo; Astikainen, Piia (Frontiers in Psychology, 2011)
Understanding speech is based on neural representations of individual speech sounds. In humans, such representations are capable of supporting an automatic and memory-based mechanism for auditory change detection, as reflected by the mismatch negativity of event-related potentials. There are also findings of neural representations of speech sounds in animals, but it is not known whether these representations can support the change detection mechanism analogous to that underlying the mismatch negativity in humans. To this end, we presented synthesized spoken syllables to urethane-anesthetized rats while local field potentials were epidurally recorded above their primary auditory cortex. In an oddball condition, a deviant stimulus /ga/ or /ba/ (probability 1:12 for each) was rarely and randomly interspersed between frequently presented standard stimulus /da/ (probability 10:12). In an equiprobable condition, 12 syllables, including /da/, /ga/, and /ba/, were presented in a random order (probability 1:12 for each). We found evoked responses of higher amplitude to the deviant /ba/, albeit not to /ga/, relative to the standard /da/ in the oddball condition. Furthermore, the responses to /ba/ were higher in amplitude in the oddball condition than in the equiprobable condition. The findings suggest that anaesthetized rat’s brain can form representations of human speech sounds, and that these representations can support the memory-based change detection mechanism analogous to that underlying the mismatch negativity in humans. Our findings show a striking parallel in speech processing between humans and rodents and may thus pave the way for feasible animal models of memory-based change detection.